Social Service (PKM) of Women’s Group of Family Welfare and Empowerment in Cultivating Broiler Rabbits and Processing them in RT. 04 RW. 03, Cipayung Village: PKM Kelompok Ibu PKK Budidaya Kelinci Pedaging dan Cara Pengolahannya di RT. 04 RW. 03 Kelurahan Cipayung - Mursito, Hardian; Awaludin, Aulia Ar Rakhman; Nedeak, Theresia Evy Yulianti (Mattawang: Jurnal Pengabdian Masyarakat, 2020)
In general, the residents of RT 004 RW 03 have a level of education at the junior and senior high school levels. This is due to the economic factors and the absence of encouragement from parents for their children to continue their education to a higher level. Moreover, women who do not continue their education at school are unemployed or decide to become housewives, because they do not have the skills to live independently. Most of the mothers are only housewives who only take care of their children and husbands. This condition cannot improve the economic condition of the family that is not fixed and coupled with the high economic burden that requires each family to be able to think creatively in order to survive amid the economic pressure. The objectives of this community service activity included: Assisting women’s group of Family Welfare and Empowerment in the formation of business groups, assisting women’s group of Family Welfare and Empowerment on how to utilize and cultivate the broiler rabbits as a small entrepreneur. The implementation of this training activity was expected to help in fostering an entrepreneurial spirit in rabbit cultivation for underprivileged people through the formation of a small business group of women of Family Welfare and Empowerment and in the form of published scientific articles. Abstrak Warga masyarakat yang berada di RT 004 RW 03 pada umumnya adalah lulusan SMP dan SMU. Hal tersebut disebabkan oleh faktor ekonomi dan tidak adanya dorongan dari orang tua agar anak-anak mereka melanjutkan pendidikan ke jenjang yang lebih tinggi. Terlebih anak perempuan yang tidak melanjutkan sekolah akhirnya menganggur atau hidup berumah tangga, karena mereka tidak mempunyai bekal keterampilan untuk bisa hidup mandiri. Sebagian besar ibu-ibu hanya sebagai ibu rumah tangga yang hanya mengurusi anak dan suaminya. Kondisi ini tidak dapat memperbaiki kondisi ekonomi keluarga, penghasilan yang tidak tetap dan ditambah beban ekonomi yang tinggi menuntut setiap keluarga untuk dapat berfikir kreatif agar dapat bertahan hidup ditengah himpitan ekonomi. Tujuan dari kegiatan pengabdian masyarakat ini antara lain: Membantu Ibu PKK dalam pembentukan kelompok usaha yang harus dibentuk, membantu Ibu PKK dalam cara pemanfaatan dan pengolahan kelinci pedaging sebagai wirusaha kecil. Diharapkan setelah kegiatan pelatihan ini dilaksanakan menumbuhkan semangat berwirausaha budidaya kelinci bagi masyarakat prasejahtera melalui pembentukan kelompok usaha kecil ibu PKK dan berupa luaran artikel ilmiah yang dipublikasikan.